A Preliminary Study: Comparative Toxicity of Extracts from Tinospora tuberculata Beumee and Lumnitzera racemosa Willd on Aedes aegypti Linnaeus Larvae (Diptera: Culicidae) - A. A. Wahizatul; R. Shasita (Universitas Gadjah Mada, 2013)
Research has been widely made on the potential use of herbal plants as effective agents for mosquito vector control. However, only a few studies have been carried out to investigate the potential insecticidal activity of mangrove plants against these dengue vectors. This study was carried out to examine the comparative toxicity of two mangrove plants, Tinospora tuberculata and Lumnitzera racemosa against the Aedes aegypti larvae. The leaf and stem of T. tuberculata and L. racemosa, were extracted using 95% methanol and these extracts bioassayed against the 3rd instar larvae of aegypti under laboratory conditions. The LC50 values of the crude extract of T. tuberculata stem and leaf were 0.5778 mg/ml and 0.7213 mg/ml, respectively. For L. racemosa, the LC50 value for stem was 1.2833 mg/ml and 1.1957 mg/ml for leaf. However, no significant differences in toxicity were detected for the stem and leaf of both plants. Both plants, especially T. tuberculata might contain insecticidal components toxic to larvae of Ae aegypti.